VOICE AND SPEECH IN PARKINSON’S DISEASE: CLINICAL CHARACTERISTICS OF HYPOKINETIC DYSPHONIA - Ilic Savic, Ivana; Petrović-Lazić Mirjana; Babac, Snežana (HEALTH CARE, 2026)
Parkinson’s disease is a chronic, progressive neurodegenerative disease that is primarily manifested by motor disorders, but significantly affects voice and speech. One of the frequent and clinically significant manifestations of the disease is hypokinetic dysphonia, which occurs as a result of central dopaminergic deficit and hypokinesia of muscles involved in respiration, phonation and articulation. The aim of this review is to present the basic neurological and clinical characteristics of Parkinson’s disease, the mechanisms of hypokinetic dysphonia, as well as the voice, speech and paralinguistic characteristics of patients with this disease, while considering the implications for clinical and speech therapy practice. The search for relevant sources was carried out using Google Scholar Advanced Search and the Consortium of Libraries of Serbia for Unified Procurement (KoBSON), where modern sources from the fields of neurology, phoniatrics and speech therapy were analyzed. The results of the review indicate that voice and speech disorders, including hypophonia, monotony, reduced intonation variation and disorganized prosody, significantly impair communication and the quality of life of sufferers. Paralinguistic communication deficits, which contribute to the social isolation of patients, are especially pronounced. It is concluded that timely recognition of hypokinetic dysphonia and an interdisciplinary approach, along with active involvement in speech therapy treatment, is of key importance for preserving communication skills and improving the overall functioning of people with Parkinson’s disease.